Monoclonal antibodies currently in Phase II and III trials for multiple myeloma. (August 2014) - Donato, Francesca; Gay, Francesca; Bringhen, Sara; Troia, Rossella; Palumbo, Antonio
Abstract : Introduction: Despite the introduction of novel agents, such as thalidomide, lenalidomide and bortezomib, multiple myeloma (MM) remains an incurable disease and new therapies are needed. mAbs are a new promising anticancer treatment option. Areas covered: This review will focus on mAbs that are currently under evaluation in Phase II and III clinical trials, as single agent and in combination with established treatment options. Expert opinion: mAbs are a new strategy against MM, and they have demonstrated encouraging results in preclinical models. mAbs have a relatively benign side-effect profile and work synergistically with traditional chemotherapies and with immunomodulatory drugs and proteasome inhibitors.